A feminist reading of debt - Cavallero, Luci; Gago, Verónica; Mason-Deese, Liz; Bhattacharya, Tithi (London : Pluto Press, 2021)
Cavallero and Gago develop a feminist understanding of debt, showing its impact on women and members of the LGBTQ+ community and examining the relationship between debt and social reproduction. Exploring the link between financial activity and the rise of conservative forces in Latin America, the authors demonstrate that debt is intimately linked to gendered violence and patriarchal notions of the family. Yet, rather than seeing these forces as insurmountable, they also show ways in which debt can be resisted, drawing on concrete experiences and practices from Latin America and around the world. Featuring interviews with women in Argentina and Brazil, the book reveals the real-life impact of debt and how it falls mainly on the shoulders of women, from the household to the wider effects of national debt and austerity. However, through discussions around experiences of work, prisons, domestic labour, agriculture, family, abortion and housing, a narrative of resistance emerges. --
Introduction: Taking debt out of the closet -- Diagnosing forms of violence -- Exploitation and difference -- A feminist reading of debt -- Debt and social reproduction -- Financial extractivism and dispossession -- What is debt? -- New era : financial terror -- Debt as a "counter-revolution" of everyday life -- The writing on the body of women -- Neither victims nor entrepreneurs -- Feminist insubordination and fascist neoliberalism -- Counter-offensive -- Gentlemen's agreement -- The patriarchy has my missing contributions -- Debt and urban development in the city of Buenos Aires -- From finance to bodies -- Voluntary termination of debt -- Hunger and gender mandates -- The debt of care -- A feminist analysis of inflation -- How to disobey finance? -- We want ourselves alive and debt free? -- Us against debt -- "They owe us a life" -- A feminist strike against debt : 2020 -- Excursus. Rosa Luxemburg : in the land of debt and consumption -- Some milestones of a brief chronology -- Interviews -- Manifestos.
Includes bibliographical references (pages 84-86) and index.
In English, translated from Spanish.
Description based on online resource; title from digital title page (viewed January 19, 2024).
JSTOR
Keywords: Women -- Finance, Personal; Debt; Feminism -- Argentina; Debt -- Argentina; Sex discrimination against women; Women -- Economic conditions; Femmes -- Finances personnelles; Dettes; Féminisme -- Argentine; Dettes -- Argentine; Discrimination à l'égard des femmes; Femmes -- Conditions économiques.; Feminism & Feminist Theory; Labor; BUSINESS & ECONOMICS; Domestic Partner Abuse; Abuse; FAMILY & RELATIONSHIPS; Economic Policy; Public Policy; POLITICAL SCIENCE; Political Advocacy; Political Process; Women in Politics; Women's Studies; SOCIAL SCIENCE; Discrimination & Race Relations; Gender Studies; Prostitution & Sex Trade; Debt; Women -- Finance, Personal; Women; Gender identity; Gender; Electronic books